2014
DOI: 10.1182/blood-2014-05-577627
|View full text |Cite|
|
Sign up to set email alerts
|

The role of FDG-PET in defining prognosis of Hodgkin lymphoma for early-stage disease

Abstract: Given the excellent survival rates for early-stage Hodgkin lymphoma (HL), the young age of many patients, and concerns regarding acute and late treatment-related toxicities, there is a desire to have a predictive tool that enables therapy to be tailored toward the individual patient. Early (or interim) 18F-fluorodeoxyglucose positron emission tomography with computerized tomography (FDG-PET/CT), as a test of tumor sensitivity to ongoing/planned therapy, has been shown to be prognostic for survival in HL. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…An important research goal is early identification of patients with poor prognosis, who could take advantage of an intensified therapy scheme. Interim 18F-Fluoro-deoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) imaging after the first two cycles of ABVD has proved to be a powerful prognostic tool in patients with HL [1][2][3]. A 5-point scoring system using the Deauville criteria (5p-Deauville Score, 5p-DS) has been proposed as a qualitative visual method to evaluate interim FDG-PET/CT and been widely accepted to be the best predictor of outcome [4].…”
Section: Introductionmentioning
confidence: 99%
“…An important research goal is early identification of patients with poor prognosis, who could take advantage of an intensified therapy scheme. Interim 18F-Fluoro-deoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) imaging after the first two cycles of ABVD has proved to be a powerful prognostic tool in patients with HL [1][2][3]. A 5-point scoring system using the Deauville criteria (5p-Deauville Score, 5p-DS) has been proposed as a qualitative visual method to evaluate interim FDG-PET/CT and been widely accepted to be the best predictor of outcome [4].…”
Section: Introductionmentioning
confidence: 99%
“…In stage I-IIA a joint American-Canadian study showed that freedom from disease progression was superior in patients achieving a complete or unconfirmed complete remission after two cycles of ABVD (P = 0.007; 5-year survival estimates, 95 vs 81 %) than those who did not after completing therapy with two more cycles with no ensuing RT [42]. Compared to traditional radiological imaging by CT, FDG-PET/CT may provide further prognostic information combining morphological (tumour shrinkage) and functional (in vivo evaluation of chemo-sensitivity) parameters to assess early treatment response [43]. However, there are comparatively much less data on the predictive role on long term treatment outcome of interim PET in early as compared to advancedstage HL, and results are controversial.…”
Section: Predicting Treatment Outcome In Hodgkin Lymphomamentioning
confidence: 95%
“…11 Corresponding Ann Arbor stages were assigned, and in case of no residual tumor on 18 F-FDG-PET/ CT after diagnostic biopsy, Ann Arbor stage was defined as stage I. In this subgroup, CT Ann Arbor stage was compared with 18 F-FDG-PET/CT Ann Arbor stage (gold standard).…”
Section: Image Analysismentioning
confidence: 99%
“…In the subgroup of 23 patients who underwent CT scanning with use of a PET/CT system (Siemens Healthcare Biograph 40 True Point PET/CT [n = 20] and Philips Healthcare Gemini TOF PET/CT [n = 3]), 18 F-FDG-PET/CT scanning was also performed. Patients fasted for at least 6 hours, and blood glucose levels were checked to be less than 11 mmol/L before 3 MBq/kg FDG was administered intravenously.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation